The Implementation of the Social Licence to Operate (SLO) Concept in Nickel Mining Governance in Kolaka Regency - Ham, Umirul (PCD Journal, 2025)
This article examines the governance of nickel mining permits in Indonesia, with Kolaka regency as a case study, with a focus on the implementation of the social license to operate (SLO) and the principle of free, prior, and informed consent (FPIC) as an integral component of SLO. The growing global demand for nickel has led to environmental degradation and social challenges. Drawing on document analysis, field observations, and interviews, this study finds that the implementation of SLO in Kolaka has not fully achieved genuine social legitimacy. Companies largely depend on corporate social responsibility (CSR) and community development programmes to build social acceptance, with primary focus on compensatory measures such as infrastructure or employment. However, these strategies tend to be top-down and do not ensure inclusive participation. FPIC has not been properly implemented, as consultations often exclude indigenous communities and fail to meet the criteria of being free, prior, and informed. Moreover, SLO is typically secured after mining operations have already commenced. These findings show that SLO implementation in Kolaka remains superficial, shaped more by CSR than by active engagement and voluntary consent from affected communities. It recommends adopting a more transparent and participatory approach grounded in FPIC principles.